2021
DOI: 10.3233/nre-201535
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive changes in muscle activity after cryotherapy treatment: Potential mechanism for improvement the functional state in patients with multiple sclerosis

Abstract: BACKGROUND: The available literature lacks data about the influence of whole body cryotherapy (WBC) on muscle activity in patients with sclerosis multiplex (MS). OBJECTIVE: Assessment of the influence of the 20 WBC series on the surface electromyography (sEMG) signal and the relationship between it and the functional state in patients with MS. METHODS: The study group was 114 of MS patients (aged 45.24±11.88yr.,) which 74 of them received 20 of WBC. An assessment was made of: the hand grip (HGS), Timed 25-Foot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…In studies of human muscle activity, information such as temperatures of skin and muscle have an apparent effect on the sEMG signals [9][10][11][12][13][14]. Figuring out this effect is crucial and may provide additional guidance for the muscle thermotherapy [15][16][17] and cryostimulation therapy [18][19][20][21][22][23][24]. To fulfill the need of temperature measurement, incorporating resistance temperature sensors into the electronic skin patch with electrodes is a simple yet efficient solution.…”
Section: Introductionmentioning
confidence: 99%
“…In studies of human muscle activity, information such as temperatures of skin and muscle have an apparent effect on the sEMG signals [9][10][11][12][13][14]. Figuring out this effect is crucial and may provide additional guidance for the muscle thermotherapy [15][16][17] and cryostimulation therapy [18][19][20][21][22][23][24]. To fulfill the need of temperature measurement, incorporating resistance temperature sensors into the electronic skin patch with electrodes is a simple yet efficient solution.…”
Section: Introductionmentioning
confidence: 99%
“…Another study by Radecka et al showed that after WBC there was an increase in the amplitude of the extensor carpi radialis (ECR) and a decrease in the amplitude of the flexor carpi radialis (FCR), with significant differences in the resting sEMG signals between the ECR and the FCR. They also found an increase in handgrip strength (HGS), an improvement in gait, and a decrease in fatigue [55]. On the other hand, Lubkowska et al only found an improvement in the strength of the right thumb [57].…”
Section: Functional Evaluationmentioning
confidence: 98%
“…Furthermore, a study by Radecka et al, which was the first to investigate the potential influence of WBC on muscle activity in patients with MS, showed an improvement in the functional status of MS patients, with a reduction in fatigue and an increase in grip strength and walking speed after 20 WBC exposures (2-3 min, at −110 • C) compared to the control group [55]. The improvement in functional status and the decreased fatigue in MS patients after daily sessions of WBC might be ascribed to adaptive changes in bioelectrical muscle activity, although the lack of studies on the subject makes further research necessary.…”
Section: Physical Functional and Psychological Parametersmentioning
confidence: 99%
“…MS is also one of the most common causes of neurological disability in young adults globally and is characterised by symptoms such as motor problems, weakness, tremors, and spasticity leading to limitations in walking, functional mobility and fatigue. 1 , 2 Fatigue represents one of the most important clinical challenges in managing MS because it affects up to 83% of patients and strongly impacts daily functioning and quality of life. 3 A standardised taxonomy that distinguishes the two major dimensions of fatigue perception of fatigue and performance fatigability was established in 2013.…”
mentioning
confidence: 99%